1998
DOI: 10.1590/s0100-879x1998000900012
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous vasopressin and the central control of heart rate during dynamic exercise

Abstract: The present article contains a brief review on the role of vasopressinergic projections to the nucleus tractus solitarii in the genesis of reflex bradycardia and in the modulation of heart rate control during exercise. The effects of vasopressin on exercise tachycardia are discussed on the basis of both the endogenous peptide content changes and the heart rate response changes observed during running in sedentary and trained rats. Dynamic exercise caused a specific vasopressin content increase in dorsal and ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
8

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 42 publications
0
8
0
8
Order By: Relevance
“…Then, Unger and coworkers [120] provided evidence that peripherally applied VP sensitized the baro-receptor reflex by the stimulation of V2R receptors in area postrema, while centrally applied VP inhibited the baro-receptor reflex by the stimulation of central V1R receptors, inaccessible from blood. Michelini and Bonagamba [78], further demonstrated that increased concentration of VP in the nucleus of the solitary tract attenuated baro-receptor reflex sensitivity, and suggested that neuronal projections from PVN might be involved in exercise-induced increases of BP [121, 122] Moreover, Morris and collaborators [123] found that OT containing neurons in PVN mediate stress-induced tachycardia. It was also shown that centrally injected VP attenuated reflex bardycardia and that VP antagonists enhanced it [124].…”
Section: Neurogenic Control Of the Cardiovascualr System By Vasopressmentioning
confidence: 99%
“…Then, Unger and coworkers [120] provided evidence that peripherally applied VP sensitized the baro-receptor reflex by the stimulation of V2R receptors in area postrema, while centrally applied VP inhibited the baro-receptor reflex by the stimulation of central V1R receptors, inaccessible from blood. Michelini and Bonagamba [78], further demonstrated that increased concentration of VP in the nucleus of the solitary tract attenuated baro-receptor reflex sensitivity, and suggested that neuronal projections from PVN might be involved in exercise-induced increases of BP [121, 122] Moreover, Morris and collaborators [123] found that OT containing neurons in PVN mediate stress-induced tachycardia. It was also shown that centrally injected VP attenuated reflex bardycardia and that VP antagonists enhanced it [124].…”
Section: Neurogenic Control Of the Cardiovascualr System By Vasopressmentioning
confidence: 99%
“…Essas complicações não estão diretamente relacionadas ao aumento da pressão arterial (PA), mas a mudanças estruturais no coração e nos vasos sanguíneos, sendo que o mais importante fator que contribui para a elevação da pressão arterial sistólica (PAS) é a rigidez arterial (BACON et al, 2004). , 1986;DAMPNEY, 1994;MICHELINI, 1998 Externamente à lâmina elástica externa encontra-se a adventícia, que consiste de fibroblastos, fibras colágenas de diâmetro largo, fibras elásticas, tecido adiposo e proteoglicanas. Semelhante à composição das túnicas íntima e média, na adventícia o colágeno tipo I corresponde a 14% do peso da adventícia, o tipo III a 7%, e água, proteoglicanas, componentes celulares, outros colágenos e elastina a 78% do peso da íntima (SILVER et al, 2001).…”
Section: Ao Meu Pai (Em Memóriaunclassified
“…Dentre os receptores periféricos destacam-se os barorreceptores arteriais, os mais importantes controladores a curto-prazo da PA (CHALMERS; MICHELINI, 1998MICHELINI, , 2001POLOWSKY, 1991;GORDON, 1994). As aferências dos barorreceptores são ativadas através do estiramento da aorta e do seio carotídeo (locais onde se situam os receptores) durante a sístole cardíaca.…”
Section: Introdução/justificativaunclassified
“…• as projeções VPérgicas do PVN ao NTS têm efeito tônico sobre o funcionamento do reflexo barorreceptor cardíaco, porque o bloqueio de receptores V1 no NTS aboliu a bradicardia reflexa, mas nenhuma alteração na sensibilidade do reflexo foi observada após administração do bloqueador V1 no líquido céfalo-raquidiano do 4º ventrículo (neurormônio), evidenciando a especificidade do efeito da VP neuronal (MICHELINI; BONAGAMBA, 1988;MICHELINI, 1994MICHELINI, , 1998 a E b);…”
Section: Introdução/justificativaunclassified
See 1 more Smart Citation